Mathematical modeling and simulation of bubble column reactor for aerial liquid phase cyclohexane oxidation - Upkare, Makarand M.; Rajurkar, Kalpendra B.; Gupta, Pankaj R.; Jaganathan, Rengaswamy (International Conference on Modeling, Optimization, and Computing, 2010)
Cyclohexane oxidation is an important but complex commercial reaction, wherein the desired product, K-A oil appears as an intermediates of the reaction sequence. A mathematical model has been developed for the bubble column reactor operating under isothermal conditions. The mass and energy model equations consisted of stiff ODEs. The model was applied to describe the behavior of bubble column reactor for aerial liquid phase cyclohexane oxidation. Effect of initial substrate concentration, catalyst loading and temperature was studied and discussed in detail. Conclusions were presented at the end of the study.
International Conference on Modeling, Optimization, and Computing, Durgapur, INDIA, OCT 28-30, 2010
Keywords: K-A Oil Selectivity; Mathematical modeling; substrate conversion and product yield analysis